Study of Intensity Variation of Naphthalene with Acetophenone and Iodine - Bakkialakshmi, S.; Shanthi, B.; Saradha, A. (Asian Journal of Chemistry, 2016)
The fluorescence of naphthalene at room temperature is polluted by the addition of acetophenone and iodine. The Stern-Volmer constants and the regression coefficient are reported. Ionization potential, electron affinity and the solvent parameter are calculated. It was found that among the two pollutants, iodine pollutes naphthalene more than acetophonone.